2020
DOI: 10.1186/s12885-020-07674-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal mapping of breast and prostate cancers in South Iran from 2014 to 2017

Abstract: Background The most common gender-specific malignancies are cancers of the breast and the prostate. In developing countries, cancer screening of all at risk is impractical because of healthcare resource limitations. Thus, determining high-risk areas might be an important first screening step. This study explores incidence patterns of potential high-risk clusters of breast and prostate cancers in southern Iran. Methods This cross-sectional study was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 71 publications
0
14
1
Order By: Relevance
“…In the last 10 years, a large number of research projects around the world have focused on early-onset CRC. The sample size of these studies ranged between 49 and 64,068 cases [5, 7-18, 48, 56-58] and the mean age of study subjects ranged between 37 and 47 years [5,[7][8][9][10][11][12][14][15][16][17][18]. In contrast to our study, the frequency of earlyonset CRC is generally reported to be higher in men than in women [5,7,10,11,[13][14][15][16][17]48], but various studies have yielded conflicting results [10,28,47,59].…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…In the last 10 years, a large number of research projects around the world have focused on early-onset CRC. The sample size of these studies ranged between 49 and 64,068 cases [5, 7-18, 48, 56-58] and the mean age of study subjects ranged between 37 and 47 years [5,[7][8][9][10][11][12][14][15][16][17][18]. In contrast to our study, the frequency of earlyonset CRC is generally reported to be higher in men than in women [5,7,10,11,[13][14][15][16][17]48], but various studies have yielded conflicting results [10,28,47,59].…”
Section: Discussioncontrasting
confidence: 71%
“…According to several studies, the incidence early-onset CRC (affecting those < 50 years of age) varies between different parts of the world with nearly 20% of the cases found in Asia including the Middle East (where the disease is not unusual in < 40-year olds) as compared to 2-8% reported in the U.S. [7,8]. The mean age of earlyonset CRC ranges between 37 and 47 years around the world [5,[7][8][9][10][11][12][13][14][15][16][17][18] and 41-69% of these cases are men. Compared to Western World (Europe and the U.S.), the incidence of CRC is currently very low in the older Iranian population, while young Iranians are showing a rising trend [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Going beyond simply ranking high values by locality, hotspot analysis identifies regional patterns with multiple adjacent localities where disparities may be harder to overcome without traveling long distances. Hotspot analysis has been used internationally, such as a Brazilian study of CRC and an Iranian study of breast and prostate cancer [ 21 , 22 ]. Examples from the U.S. include a U.S. national study to identify county clusters of high mortality rates [ 6 ] and a state-level study in Florida to identify areas with high rates of late-stage diagnoses [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analysing and interpreting the spatio-temporal transmission patterns of the virus are indispensable in order to generate the best-tailored strategies [ 6 ]. The strength of Geographic Information Systems (GIS) applications lies in their capability of mapping geographical disease distributions thereby visualizing trends of their spread, which can be utilized for modelling spatial aspects of disease occurrence in relation to the ambient environments [ 7 9 ].…”
Section: Objectivementioning
confidence: 99%